The Rugrats' Easter Surprise - Willson, Sarah; Roper, Robert (New York : Simon Spotlight/Nickelodeon, 2002)
"It's springtime and love is in the air! Even Tommy's dog, Spike, has fallen for Kimi's dog, Fifi..."
"Nicklodeon Rugrats"--Cover.
82201
Keywords: Rugrats (Television program) -- Fiction; Babies -- Fiction; Easter -- Fiction; Babies -- Juvenile fiction; Love -- Juvenile fiction; Puppies -- Juvenile fiction; Easter -- Juvenile fiction